2022
DOI: 10.3389/fphar.2021.789640
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions About Biosimilar Medicines Among Belgian Patients in the Ambulatory Care

Abstract: Background and objectives: Biosimilar medicines have been on the European market for 15 years. Despite the extensive and positive experience with biosimilars across Europe, their uptake remains limited in Belgium. One of the possible factors limiting uptake in clinical practice is the inadequate understanding and lack of trust in biosimilars among patients. This study aimed to assess the level of knowledge and perceptions about biosimilar medicines among Belgian patients in the ambulatory care.Methods: This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…A contributing factor to these concerns could be the participants' challenge in understanding the complexity of biologics, which is reflected in that almost all participants were unaware that biosimilars are different from generics. This contrasts Aladul et al where patients were well‐informed and showed high understanding of biosimilars 11 ; however, low biosimilar awareness has been reported previously 9,23–26 . Those gaps in knowledge could explain the observed low willingness to switch to a biosimilar among our informants.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…A contributing factor to these concerns could be the participants' challenge in understanding the complexity of biologics, which is reflected in that almost all participants were unaware that biosimilars are different from generics. This contrasts Aladul et al where patients were well‐informed and showed high understanding of biosimilars 11 ; however, low biosimilar awareness has been reported previously 9,23–26 . Those gaps in knowledge could explain the observed low willingness to switch to a biosimilar among our informants.…”
Section: Discussioncontrasting
confidence: 76%
“…Such communication to patients should be made by healthcare professionals as these are trusted information sources for patients. 24,26,29 However, it is also important to develop patient education material based on recommendations to ensure its effectiveness, such as developing tailored information, delivered in a relevant format and by competent HCPs. [30][31][32] Further research is needed to compare prescribers' and patients' perspective on available patient educational information to identify potential gaps and differences in understanding of the materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients, less adequate understanding of biosimilars was found in comparison with HCPs ( p < 0.01). Only 50.98% of the patients chose the correct definition, which showed a similar inadequate level of knowledge about biosimilars to several published studies ( Peyrin-Biroulet et al, 2017 ; Azevedo et al, 2018 ; Vandenplas et al, 2021a ). This emphasizes an existing knowledge gap and the further need for tailored education for patients.…”
Section: Discussionmentioning
confidence: 52%
“…Based on the results of our current study, several recommendations might be considered to fill the gap between the knowledge, attitude and uptake of biosimilars. As studies showed medical staff are the most trusted source of information about biosimilars for patients ( Peyrin-Biroulet et al, 2017 ; Vandenplas et al, 2021a ), it is necessary for HCPs to conduct patient education about biosimilars to promote uptake. Specific strategies for educating patients about biosimilars have already been proposed in some studies ( Vandenplas et al, 2021b ; Oskouei and Kusmierczyk, 2021 ).…”
Section: Discussionmentioning
confidence: 99%